2022
DOI: 10.3390/life12111899
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmological Approach for the Diagnosis of Dry Eye Disease in Patients with Sjögren’s Syndrome

Abstract: Dry eye has two basic subdivisions: aqueous deficient dry eye (ADDE), with SS a major cause; and evaporative dry eye (EDE), due to either intrinsic or extrinsic factors. SS is a chronic inflammatory disorder defined by dysfunction of the exocrine glands leading to dry eye and dry mouth. The objective of this article was to carry out a systematic and critical review of several scientific publications on dry eye disease, with the aim of providing general recommendations to distinguish dry eye and its different v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 90 publications
0
8
0
Order By: Relevance
“…Some studies on Sjogren syndrome and Rheumatoid arthritis reported the prevalence of dry eye about 23 per 1000 person-years. 10,11 MS disease pathogenesis has integral parts of the inflammatory cytokines secreted by Th1 and Th17, resulting in increased blood-brain barrier permeability to monocytes and macrophages. Th1 cells are found in damaged parts of the CNS and are actively present in MS patients' bloodstream, which produces inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on Sjogren syndrome and Rheumatoid arthritis reported the prevalence of dry eye about 23 per 1000 person-years. 10,11 MS disease pathogenesis has integral parts of the inflammatory cytokines secreted by Th1 and Th17, resulting in increased blood-brain barrier permeability to monocytes and macrophages. Th1 cells are found in damaged parts of the CNS and are actively present in MS patients' bloodstream, which produces inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the present non-invasive diagnostic methods lack the necessary specificity and sensitivity, resulting in SS diagnosis involving invasive gland biopsy and functional assessments [44]. As a result, many have researched alternative non-invasive and disease-specific diagnostic tools to provide a quicker diagnostic while enabling treatment monitoring [41,45].…”
Section: Novel Diagnostic Methodsmentioning
confidence: 99%
“…In short, innovative diagnostic methodologies have emerged, holding transformative potential for the timely, non-invasive, and accurate diagnosis of SS. Thanks to advances like immunoaffinity mass spectrometry, the analysis of serum, saliva, and tear proteomics has become more accessible, permitting accurate quantification of specific proteins implicated in SS [45]. Unveiling the underlying pathways and proteins in SS pathogenesis has led to the identification of promising biomarkers, including CXCL10, MUC5AC, the JAK-STAT signaling pathway, MMP-9, and miRNA derived from exosomes.…”
Section: Barriers To Clinical Translation: the Gap Between Innovation...mentioning
confidence: 99%
“…The constellation of autoantibodies (particularly antinuclear anti-Ro/SS-A and anti-La/SS-B) indicates a loss of B cell tolerance along with dysregulated activity in the interleukin (IL)-1 system. The disease has detrimental clinical, quality-of-life, and financial burdens on patients [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%